Strategi Diversifikasi Korporat, Struktur Modal dan Nilai Perusahaan (Studi pada Perusahaan yang Tercatat di Bursa Efek Indonesia) - Siti Aisjah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research is conducted to evaluate and examine the corporate diversification strategy, capttal structure and company value based on balance approach TradeOff Theory and Pecking Order Theory. The diversification index (related and unrelated) was determined based on HierschmanHerfindahl index. The capital structure variable consists of assets utilisation, bankruptcy cost, company s growth and dividend policy. The research also examines company rationalities in doing corporate diversification strategy, capital structure and their influence toward company value. The population of the research consists of the companies registered in Indonesia Stock Exchange. The samples were taken using purpose sampling technique. Based on the determined criteria, 43 sample fulfilling the criteria were obtained with six year observation period (in 20022007) and 253 observations. The research findings showed that the related and unrelated diversification strategy influenced the capital structure and company value. The attitude of the companies registered in Indonesia supported the Pecking Order Theory in related diversification and unrelated diversification companies. These are the efforts of companies to prioritize internal fund resources coming from free cash stream in order to reduce business risk. The capital structure policy in effort to increase company value the companies need to consider corporate diversification strategies, both related and unrelated.